Bioaugmentation with Endophytic Bacterium E6S Homologous to Achromobacter piechaudii Enhances Metal Rhizoaccumulation in Host Sedum plumbizincicola - Ma, Ying; Zhang, Chang; Oliveira, Rui S.; Freitas, Helena; Luo, Yongming (Frontiers in Plant Science, 2016)
Application of hyperaccumulator–endophyte symbiotic systems is a potential approach to improve phytoremediation efficiency, since some beneficial endophytic bacteria are able to detoxify heavy metals, alter metal solubility in soil and facilitate plant growth. The objective of this study was to isolate multi-metal resistant and plant beneficial endophytic bacteria and to evaluate their role in enhancing plant growth and metal accumulation/translocation. The metal resistant endophytic bacterial strain E6S was isolated from stems of the Zn/Cd hyperaccumulator plant Sedum plumbizincicola growing in metalliferous mine soils using Dworkin and Foster salts minimal agar medium with 1-aminocyclopropane-1-carboxylate (ACC) as the sole nitrogen source, and identified as homologous to Achromobacter piechaudii based on morphological and biochemical characteristics, partial 16S rDNA sequence and phylogenetic analysis. Strain E6S showed high level of resistance to various metals (Cd, Zn and Pb). Besides utilizing ACC, strain E6S exhibited plant beneficial traits, such as solubilization of phosphate and production of indole-3-acetic acid. Inoculation with E6S significantly increased the bioavailability of Cd, Zn and Pb in soil. In addition, bacterial cells bound considerable amounts of metal ions in the following order: Zn ˃ Cd ˃ Pb. Inoculation of E6S significantly stimulated plant biomass, uptake and bioaccumulation of Cd, Zn and Pb. However, E6S greatly reduced the root to shoot translocation of Cd and Zn, indicating that bacterial inoculation assisted the host plant to uptake and store heavy metals in its root system. Inoculation with the endophytic bacterium E6S homologous to A. piechaudii can improve phytostabilization of metalliferous soils due to its effective ability to enhance in situ metal rhizoaccumulation in plants.